2013
DOI: 10.1177/1060028013508085
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Procalcitonin as a Biomarker for Rejection and Differentiation of Infectious Complications in Lung Transplant Recipients

Abstract: Current data suggest that PCT can be used to differentiate bacterial infections from rejection in lung transplant recipients, with unclear utility in colonization or fungal infection. It is reasonable to conclude that PCT values more than 8.18 ng/mL and PCT area under receiver operating curve greater than 0.97 indicate bacterial infection in this population, and PCT trends may increase predictive value. Because of the lack of randomized controlled trials, PCT should only be utilized in conjunction with standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
1
13
2
Order By: Relevance
“…In contrast, PCT is produced in C cells of the thyroid gland and by neuroendocrine cells of the lung and the intestine [12,13]. However, PCT is more a marker for bacterial than for viral infections [14][15][16]. Furthermore, it is possible that we here did not detect any statistical significance because the maximal increase of PCT might be at a later than fours days after OLT.…”
Section: Discussioncontrasting
confidence: 51%
“…In contrast, PCT is produced in C cells of the thyroid gland and by neuroendocrine cells of the lung and the intestine [12,13]. However, PCT is more a marker for bacterial than for viral infections [14][15][16]. Furthermore, it is possible that we here did not detect any statistical significance because the maximal increase of PCT might be at a later than fours days after OLT.…”
Section: Discussioncontrasting
confidence: 51%
“…Studies have shown that PCT can effectively diagnose infectious complication among solid organ transplant recipients [30][31][32]. Unfortunately, these studies were sporadic and there were few analyses focusing on single organ, liver, for example.…”
Section: Discussionmentioning
confidence: 99%
“…Blood, plasma or serum: Multiple studies have attempted to identify biomarkers of rejection in the peripheral blood, focusing on cell subsets, proteins, or transcripts. 126,[143][144][145][146] However, most of these studies have been negative or nonreproducible, suggesting that the ACR signal in the peripheral circulation is not detectable using most techniques. A new, more sensitive method to detect donor-derived circulating cell-free DNA (cfDNA) is considered particularly promising for the noninvasive monitoring of allograft injury.…”
Section: Histologic Diagnosismentioning
confidence: 99%